Ushering Modernity in Kerala: A Critique of The Slayer Slain - Asha Susan Jacob (IJELLH, 2018)
A close appraisal of the first-generation novels in Malayalam offers seminal insights into the spatio-temporal settings of Kerala at the dawn of Modernity. The exposure to new systems of learning ushered in by colonialism and missionary endeavour, coupled with the encouragement of the native rulers, spearheaded sweeping changes in the multi-layered social, cultural and political scenario,impacting particularly on the lives of those on the peripheries, the lower caste and the female.The paper attempts a critique of The Slayer Slain, one of the earlier attempts in the imported genre of the novel,in its presentation of the imprint of modernity in a land of caste and community divisions.